KONSEP MUSIK JAZZ FUSION BALI PADA KOMPOSISI SANGHYANG LEGONG KARYA INDRA LESMANA - Fardian, Fardian (Institut Seni Indonesia (ISI) Surakarta, 2023)
Jazz Fusion music is one of the music styles currently developing in Bali. The characteristics of Jazz Fusion include combining two musical concept approaches, between local music concepts (Balinese tradisi) and foreign music (western), which results in a different Jazz musical identity. One musical work, Sanghyang Legong, describes the situation of Balinese Jazz Fusion music. Sanghyang Legong musical work results from a collaboration between famous Indonesian jazz musician Indra Lesmana and Balinese gamelan musicians I Made Subandi (alm.) and I Wayan Sudiarsa. This work uses Gending Sanghyang as a source of inspiration developed through a jazz music aesthetic approach. This composition received great appreciation from the music community inside and outside Bali. After being mass-produced in 2017, Sanghyang Legong attracted over 36,000 monthly views on YouTube, Spotify, and Apple Music. This article aims to educate the reader on the composer’s creative process, the resultant musical form, and the work’s significance. The formulation of the problem includes (1) the process of creation, (2) musical form, and (3) implications of Sanghyang Legong composition. The research method uses a qualitative design with a descriptive approach to musicology. Data collection through documentation and interviews. Analysis through the stages of data reduction, data presentation, and conclusion. The elaboration of instruments and playing techniques of Gamelan Singapraga, Suling (Balinese Flute), and Balinese Gending Vocal Style showed the concept of Jazz Fusion music in the composition of Sanghyang Legong. The song has five parts: Solo, Intro, Verse, Chorus, and Interlude. This work has an impactful implication for the sustainability of tourism and Bali’s creative economy.